A spatial dataset of topsoil texture for the southern Argentine Pampas - Castro Franco, Mauricio (2018)
We produced a 1-km spatial resolution dataset of soil texture for the southern Argentine Pampas. Variables related to climate have higher prediction performance for soil texture. The soil texture varies gradually becoming finer westward. Prediction of soil properties in the Argentine Pampas can be improve using DSM techniques.